Openness Without Safety? Negotiated Visibility, Stigma, and Well-Being Among Female Sex Workers Living in Local Communities - Riki Grahambel Palar; Arthur Huwae (Utan Kayu Publishing, 2026)
Female sex workers (FSWs) often manage a concealable, stigmatized identity, yet some are known within their neighborhoods. Using Interpretative Phenomenological Analysis (IPA), this study examined how five Indonesian FSWs (35–45 years) living in Central Java made sense of “living openly” and mental health as emotional, psychological, and social well-being. “Living openly” was defined as negotiated openness: at least some community members (e.g., neighbors, informal leaders, and/or family) knew participants’ work status, while operational details were deliberately withheld. Participants were recruited via snowball sampling and completed in-depth interviews in Indonesian; excerpts were translated into English for reporting. Idiographic accounts converged in four cross-case themes: (1) boundary work that eased the burden of secrecy without requiring total disclosure; (2) emotional relief coexisting with vigilance as stigma resurfaced through gossip, moral judgment, harassment, and safety concerns; (3) psychological well-being sustained by time–space separation between work and home, privacy management, selective trust, and meaning anchored in caregiving roles; and (4) social well-being built through routine participation and visible contribution to community activities under conditional acceptance. The findings position openness as a continuing social practice through which well-being is reconstructed amid persistent stigma and structural vulnerability. Implications highlight harm-reduction norms, safe spaces, and family support.